Decrease of central venous catheter-related infections by implementing simple low cost interventions in an pediatric intensive critical care unit - Nakachi-Morimoto, Graciela (2017)
Objective: To decrease the nosocomial central line–associated bloodstream infections (CLABSI) implementing simple low cost evidenced-based interventions in a pediatric intensive care unit. Design: Prospective cohort study. Setting: Pediatric Intensive Care Unit, Instituto Nacional de Salud del Niño (INSN), Lima, Perú. Methods: All patients less than 18 years of age with central venous catheter in the PICU were evaluated, from 2009 to 2012. A basal measure was performed from 2007 to 2010. During the project, from 2011 to 2012, simple, low cost measures were implemented. Main outcome measures: Rate of catheter line associated bloodstream infection (CLABSI) per 1 000 catheter days. Results: During the pre-project period (2007-2010), 1 047 patients with CVC were followed during 9 303 catheter-days; 60 patients presented CLABSI, and the average annual CLABSI rate was 6.03 (10.01, 5.33, 3.28 y 5.49 respectively per year). During the project, 267 patients were followed, with 2 303 catheter-days; 4 patients presented CR-BSI, with an average annual rate of 1.7. In 2011, an estimation of nine CLABSI that could have been prevented gave an estimated cost of 338 364 soles per year. Conclusions: There was a constant decrease of CR-BSI in the PICU during the months of implementation of the project. The simple, low cost measures decreased the average annual rate of CLABSI to 1.7.